A finite element study on femoral locking compression plate design using genetic optimization method. (July 2022) - Rostamian, R.; Silani, M.; Ziaei-Rad, S.; Busse, B.; Qwamizadeh, M.; Rabczuk, T.
Abstract: The locking compression plate (LCP) and screw sets are widely used as internal fixator assemblies to treat long bone fractures. However, the surgeon's critical challenge is choosing the implant set (plate and screws) for each patient. The present study introduces a parametrized simulation-based optimization algorithm for determining an LC system with the best bone-implant stability. For this purpose, a three-dimensional fractured bone supported by an LC system was generated, and the discrete genetic optimization approach was utilized to design the optimum implant. Initially, an algorithm was developed to optimize the optimum layouts for different numbers of screws. For the middle third transverse fracture, six screws were selected as the optimal number of the screws. In a second stage, the model was run to determine the best LC plate dimensions for desired fractured bones. Finally, optimal plates were identified for simple middle third transverse, 60° middle third oblique, and distal third transverse femoral fractures. The results of these simulations and those for other fracture types can be exploited to achieve improved surgical outcomes by selecting proper implants and screws configurations.